2013
DOI: 10.1136/bcr-2012-008500
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of postmenopausal bleeding

Abstract: A 68-year-old postmenopausal woman presented to the gynaecology clinic with a 1-week history of vaginal bleeding. She was investigated to rule out local and systemic causes including genital malignancy. The investigations were negative for genital malignancy and her symptoms settled spontaneously. The bleeding was attributed to a corticosteroid treatment for shoulder joint pain. A short literature review of this rare side effect is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Uncommon causes of postmenopausal bleeding include uterine fibroids, adenomyosis (often during HRT), cervical polyp and cancer, and vaginal, tubal, and ovarian cancer. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Uncommon causes of postmenopausal bleeding include uterine fibroids, adenomyosis (often during HRT), cervical polyp and cancer, and vaginal, tubal, and ovarian cancer. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…A case series reported that post-menopausal women experienced bleeding between 9 and 19 days after shoulder, knee, or bursal injections with doses ranging from 10-40 mg triamcinolone acetate. Those between the ages of 45 to 64 years were more likely to report bleeding compared to the over 65-year age group (4.5/1000 ~ 3.3/1,000), which may be due to greater degree of atrophic endometrium in the older age group (Gowri, 2013). Information should be provided as those who experience menstrual alterations may not relate it to the CS injection and may seek specialist advice (Suh-Burgmann et al, 2013).…”
Section: Menstrual Alterationsmentioning
confidence: 99%